Ensino de ciências por meio da recreação na educação infantil - Lanes, Dário Vinícius Ceccon (2011)
We live in a society impacted by science and technology, where every citizen needs a scientific-technological culture to understand, integrate and act in the world that surrounds it. Similarly, to show science as preparation for a human understanding of the world, from an early age is a goal for education at school. Thus, it becomes clear the necessity of forming reflective generations, who have the ability to critically analyze information and make responsible decisions in the context of its shares. Considering the aspects exposed, this work proposes to use and evaluate the effectiveness of recreation as a methodological tool for the Teaching of Science in Early Childhood Education, about body image issues, eating habits, gender and sexuality. This survey was conducted in three private schools in kindergarten in the city of Uruguaiana / RS, with 43 children, aged between 3 and 5 years for 3 quarters. The interventions were physical education through recreational activities, integration and cooperative games, using music, toys constructed with alternative materials, designs, pictures and foods in various presentations. It was found in the results obtained on the body schema that children in the intervention group performed better at posttest compared to controls, in the following categories: full face, trunk, upper and lower limbs. In relation to healthy eating habits, we can see in relation to pre-test, children had no notions of healthy eating habits, as quoted in the majority as an example the group of sugars, following the intervention of recreational physical education classes, group control remained with the same concepts of healthy eating and the intervention group increased the occurrence of foods considered healthy, reducing the occurrence of which are not recommended for adequate nutrition. With regard to sexuality theme, it was found that the intervention group showed a significant increase of knowledge as to the categories: female figure, painted with different colors, short hair and clothing color Girl (pink, orange, red, purple) . These data indicate better understanding by the children in relation to gender. Thus, the use of recreation facilitated the understanding on issues of gender and sexuality, because the universe of children's games are expressed as the ways the child deals with bodies of self and others, often playful ways that ultimately make up sexuality and also play from a worldview marked by gender. Therefore, the use of recreation for the children's education contributed to the development of these children, as a recreational activity, besides being very pleasant, the child takes a particular role and acts according to him, these elements being important for learning the same.